Assessment of Some Heavy Metal Pollution on Soil via E-Waste Dumping Activities and Unpolluted Soil in Abraka, Delta State, Nigeria - Eyenubo, O. B.; Peretomode, O.; Egharevba, F.; Osakwe, S. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This research investigated the concentration of heavy metals pollution of soil via e-waste dumping in Abraka community. Two soil samples were obtained and analyzed through digestion and the use of Atomic Absorption Spectrophotometer (AAS). The concentration of cobalt (Co), chromium (Cr) and manganese (Mn) on the polluted soil were higher than the control soil at depths 0 – 10 cm and 10 – 20 cm (25.55 and 22.65 mg/kg, 10.19 and 8.65 mg/kg, 78.15 and 51.16 mg/kg) and lower in depth 20 – 30 cm (10.82, 6.55 and 41.98 mg/kg). While the concentration of iron (Fe) on the polluted soil is higher than that of the control and also decreased across depths (1096.60, 652.02 and 420.43 mg/kg). The concentration of antimony (Sb) and arsenic(As) shows no much difference across the depths. Statistically, there was a much difference between the six metals (t = 0.595, p = 3.020) for cobalt, (t = 0.222, p = 1.440) for chromium, (t = 0.969, p = 25.42) for manganese, (t = 0.092, p = 71.15) for iron and (t = 0.038, p = 0.020) for both antimony and arsenic respectively. It was observed that concentration of the metals under study were lower than Dutch optimum and action values, except for Co in depths 0-10 cm and 10-20 cm. The mean and median of cobalt, chromium, manganese and iron show relatively close differences on the polluted soil at depths 0 – 10 cm and 10 – 20 cm, while at depth 20 – 30 cm, there is no relative closeness .The reverse is the case for control soil, except for antimony and arsenic which shows no pollution effects. The contamination factors for Co showed 1 < CF ≤ 3 (10-20 cm and 20-30 cm) and 1 < CF (0-10 cm), while Cr, Sb, Mn, Fe and As also show 1 < CF (0-10 cm). There is clear evidence of pollution when the concentrations of polluted and unpolluted soils were compared. As such an effort should be made by the government to monitor the indiscriminate dumping of e-waste in the community in order to avoid such pollution level.